Dinâmica do perfilhamento de azevém sob diferentes métodos de pastejo - Dotto, Lisiani Rorato (2019)
The ryegrass (Lolium multiflorum Lam.), is among the winter forage grasses the most cultivated species in Rio Grande do Sul, for being a source of preferential resources, such as a natural maintenance facility, resistance to a high potential of seed production and versatility in intercrops. Knowledge of the factors that affect pasture productivity is essential to make the production system viable. The adoption of ryegrass management strategies is of great importance to maximize plant and animal production and among these strategies the grazing methods stand out. The longevity of the tiller population in grass canopies depends on the efficient replenishment of tillers, which is affected by their appearance and death. Unbalance between them in poorly managed canopies can result in a process of grass degradation. The objective of this work to evaluate the effect of grazing methods on the tiller dynamics Italian ryegrass during grazing cycles. The experimental design was a complete randomized complete block, with repeated measurements over time two treatments (grazing methods) and three area replicates. The morphogenetic and structural variables were not altered by grazing methods and showed differences during grazing cycles. The variables appearance rate, survival rate, stability index the tiller population and site occupation suffered no differences between grazing methods, but varied between generations of tillers. The continuous grazing method favored the highest population density of tillers. The change in the plant's phenological stages interferes with the tillering dynamics, regardless of the grazing method. The population of tillers is kept stable, regardless of the grazing method used.